Principal Strategies in Strengthening Teacher Leadership for Learning Innovation and School Quality at SMP MBS Al Amin Bojonegoro - Cebeng Alhudayatul Ustadza; Nurul Zuriah; Arina Restian (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the principal’s strategies in strengthening teacher leadership to promote instructional innovation and improve school quality at SMP MBS Al Amin Bojonegoro. This research employs a qualitative descriptive approach using in-depth interviews, observations, and document analysis as data collection techniques. The findings reveal that the principal plays a role as a facilitator, motivator, and driver of an innovation culture through training programs, regular discussion forums, academic supervision, and providing opportunities for teachers’ participation in school decision-making. Teachers are encouraged to implement innovative learning models such as Problem Based Learning (PBL) integrated with interactive digital media, which enhances student engagement, creativity, and critical thinking skills in the learning process. Collaboration among the principal, teachers, and administrative staff creates positive synergy in improving the overall quality of learning in the school. Supporting factors include leadership trust, administrative support, and a collaborative school culture, while challenges involve limited time, varying student readiness, and teacher welfare issues. The study concludes that strengthening teacher leadership is an effective strategy to foster an innovative school culture and sustainably improve educational quality.